Pengaruh Pelatihan dan Pengembangan SDM terhadap Kinerja Karyawan J&T Express - Haliza, Siti Nur; Safaat, Safaat; Sari, Evi Thelia; Manafe, Leonard Ardie (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this research is to examine how employee performance at J&T Express Tambaksari District is influenced by training and human resource (HR) development. The quality of human resources (HR) has emerged as an important component in achieving organizational goals in the era of globalization and increasing corporate competition. The population of this study, which uses a quantitative approach, consists of 42 employees of J&T Express. Saturated sampling is the sampling method used. An online survey was used to collect data, and multiple linear regression was used for analysis. The study's findings indicate that although human resource development significantly improves employee performance, training does not have a recognizable effect on it. Moreover, employee performance has a positive impact when training and human resource development are conducted simultaneously. These findings are expected to provide insights for J&T Express management in designing more effective training and development programs to improve employee performance and the company's competitiveness.